Burden and predictions of hospitalized injuries in a low-middle income country: results from a Tunisian university hospital - Meriem Kacem; Cyrine Bennasrallah; Hela Abroug; Manel Ben Fredj; Imen Zemni; Wafa Dhouib; Amel Gara; Ameni Maatouk; Issam Aloui; Samir Nouira; Ines Bouanene; Asma Sriha Belguith (Libyan Journal of Medicine, 2023)
ABSTRACTInjuries are responsible for a high premature mortality and disability. They are poorly explored in low and middle income-countries. We aimed to estimate the burden of hospitalized injuries in the Monastir governorate (Tunisia) according to the nature of the injury, trends and projections of hospitalizations for injuries up until 2024, and to identify the distribution of this disease burden based on age and sex. We performed a descriptive study from 2002 to 2012 including all hospitalizations for injuries. Data were collected from morbidity and mortality register of the University Hospital of Monastir (Tunisia). We estimated the burden of injuries using the Disability Adjusted Life Years (DALYs). We described injuries (crude prevalence rate (CPR) and age standardized prevalence rate (ASR)), related mortality (lethality and standardized mortality ratio (SMR)), trends and prediction for 2024. A total of 18,632 hospitalizations for injuries representing 10% of all hospitalizations during study period were recorded. Per 1000 inhabitants per year, CPR was 3.36 and the ASR was 3.44. The lethality was of 17.5 deaths per 1000 injured inpatients per year and the SMR was of 2.95 (Confidence Interval of 95%: 2.64–3.29). Burden related to injuries was 2.36 DALYs per 1000 population per year, caused mainly by Years of Life Lost (83.4%), most frequent among men aged under 40 years. The predicted ASR for 2024 was 4.46 (3.81–5.23) per 1000 person-years. Injuries to the head was the most prevalent (20.7%) causing 67.7% of DALYs; and increasing by 226% through 2024. Injuries had a high prevalence and an important burden in a Tunisian university hospital. Prediction showed increased prevalence for 2024. Preventive measures and a trauma surveillance register should be implemented soon.